Targeting CREBRF in Cancer: Mechanistic Insights and Future Directions - Lv B; Zhang D (Biologics: Targets & Therapy)
Baixue Lv, Dongdong Zhang Department of Oncology, Xiangyang No. 1 People’s Hospital, Hubei University of Medicine, Xiangyang, Hubei, 441000, People’s Republic of ChinaCorrespondence: Dongdong Zhang, Department of Oncology, Xiangyang No. 1 People’s Hospital, Hubei University of Medicine, Jiefang Road No. 15, Xiangyang, Hubei, 441000, People’s Republic of China, Tel +8615072278600, Email zhangdongdong@whu.edu.cnAbstract: Luman/CREB3 recruitment factor (LRF), also known as CREBRF, was initially identified as a cellular binding protein of Luman through yeast two-hybrid screening of a human brain cDNA library. CREBRF plays a critical role in various biological processes, with its functions garnering significant attention in the field of oncology. Notably, CREBRF is involved in endoplasmic reticulum (ER) stress and regulates the unfolded protein response (UPR), leading to an accumulation of misfolded proteins. This can ultimately result in cellular dysfunction, apoptosis, and even tumorigenesis. In solid tumors, hypoxia is a common condition, and CREBRF has been implicated in hypoxia-induced autophagy, which promotes tumor cell proliferation. Depending on the tumor type and microenvironment, CREBRF exerts diverse effects by modulating distinct signaling pathways. This review summarizes CREBRF’s involvement in ER stress, cell cycle regulation, autophagy, and the mechanisms through which it influences tumor initiation and progression across various cancer types. Furthermore, the potential of CREBRF as a therapeutic target in cancer treatment is discussed, providing insights into future research and clinical applications.Keywords: CREBRF, ER, hypoxia, tumor, autophagy, therapeutic target